FEATURES AND DIFFICULTIES OF TRANSLATING PHRASEOLOGICAL EXPRESSIONS FROM ENGLISH INTO RUSSIAN - Gulparshin Bazarbaeva Allambergenovna (ZAMONAVIY TA'LIMDA FAN VA INNOVATSION TADQIQOTLAR, 2025)
This article discusses the peculiarities and difficulties of translating English phraseological expressions into Russian. It examines semantic, cultural, and structural challenges that arise during translation, offering strategies and examples to ensure adequate equivalence and cultural adaptation. The research aims to highlight how phraseology reflects national identity and worldview, thus emphasizing the translator’s role as a mediator between two linguistic cultures.